Animal Related Injuries - Yıldız, Mustafa; Durukan, Polat (Fırat University, 2005)
Objective: Animal related injuries are not well defined in Turkey as all over the world. Traumas due to cattle cause important health risks for the people living in rural areas. These traumas may cause blunt and penetrating injuries in various parts of the body due to high energy transfer. Materials and Methods: Data from the patients taken to the Firat University Faculty of Medicine Departrment of Emergency Medicine (ED) due to animal related injuries between January 2002 and August 2004 were recorded to the patient forms and analysed by SPSS 10.0 program. Values were expressed as percentage and standart deviation. Results: During that time period 32 patients were admitted to the ED due to animal related injuries. Bites were not included to the study. Nineteen of patients (59.4%) came due to animal related injuries. Mean age of the patients was 32.26±30.6 years. Thirteen of the patients (68.4%) were male. Injuries were most frequently seen in the first decade (36.8%). It was determined that patients had been admitted to ED quite late (mean admission time 238.15_74.2 minutes). Injuries were usually caused by horses (57.9%). The most frequent mechanism was kicking (68.4%), mostly affected site of the body was the head (73.7%). Multiple trauma was detected in six (31.6%) of the patients. Six patients (31.6%) were discharged, 11 (57.9%) were admitted to the hospital. Mean staying time in ED was 165.52±114.5 minutes. One in ED, totally three patients (15.8%) died; one due to horse kicking, two cow kicking. Most of the patients (21.1%) were admitted to neurosurgery department and mean duration of admission was 12.09±9.4 days. Nine (47.4%) of the patients were operated. Conclusion: It is important in Turkey to prevent animal related injuries. They are met very rarely in ED but cause high mortality. We think that there is not enough epidemiological data about animal related injuries.

Amaç: Hayvanlara bağlı yaralanmalar tüm dünyada olduğu gibi ülkemizde de iyi tanımlanmamıştır. Büyükbaş hayvanlardan dolayı oluşan travmalar kırsal kesimde yaşayan insanlar açısından önemli bir sağlık riski oluşturmaktadır. Bu travmalar sırasında yüksek enerji transferinden dolayı vücudun çeşitli bölgelerinde künt ve penetran yaralanmaların olabilmektedir. Gereç ve Yöntem: Fırat Üniversitesi Tıp Fakültesi Acil Servisine (AS) Ocak 2002-Ağustos 2004 tarihleri arasında hayvanlara bağlı yaralanmalar sebebiyle getirilen hastaların verileri hazırlanan forma kaydedildi. Verilerin analizi SPSS 10.0 programı kullanılarak yapıldı. Değerler yüzde ve standart sapma olarak yazıldı. Bulgular: Çalışma döneminde hayvanlara bağlı yaralanma sonucu AS'ye 32 hasta müracat etti. Isırma vakaları çalışmamıza dahil edilmedi. Hastaların 19'u (%59.4) hayvanlarla oluşan travmalardı. Yaş ortalaması 32.26±30.6 yıldı. Hastaların 13'ü (%68.4) erkekti. Yaralanmaların en sık ilk dekadda olduğu tespit edildi (%36.8). Hastaların olay sonrası AS'ye geç başvurduğu belirlendi (ortalama başvuru süresi 238.15±74.2 dakika). Yaralanmaya sebep olan hayvanlar sıklıkla atlardı (%57.9), en sık yaralanma mekanizması tekmelemeydi (%68.4) ve kafa en çok etkilenen bölgeydi (%73.7). Çoklu travma 6 (%31.6) hastada tespit edildi. Hastaların 6'sı (%31.6) taburcu edildi, 11 hastaya (%57.9) yatış verildi. AS'de kalış süresi ortalama 165.52±114.5 dakikaydı. Bir hasta AS'de olmak üzere toplam 3 (%15.8) hasta, biri at ve 2'si inek tekmelemesi nedeniyle, eksitus oldu. En sık hasta yatan klinik beyin cerrahisi (%21.1) olurken, ortalama yatış süresi 12.09±9.4 gün olarak belirlendi. Hastaların 9'una (%47.4) cerrahi tedavi uygulandı. Sonuç: Ülkemizde hayvansal kaynaklı yaralanmaların önlenmesi önem taşımaktadır. AS'de az görülmesine rağmen yüksek ölüm oranıyla dikkat çekmektedir. Ülkemizde hayvanlara bağlı yaralanmalar açısından yeterli epidemiyolojik veri olmadığını düşünmekteyiz.
Hayvanlara Bağlı Yaralanmalar